The Use of Digital Application in Enriching English Vocabulary for 7-8 Years Old Children - Dira Seviana Putri; Vivi Rachma; Haris, Safina Adnan; Mafela Lunetta Pratista (Candradimuka: Journal of Education, 2025)
The study investigates the effectiveness of the “Learn English Words with SMARTTEACHER” application in enhancing English vocabulary among Indonesian children in elementary school. This research targets young learners at an early cognitive stage and contextualizes the study within the Indonesian educational setting, where traditional methods have shown limitations in vocabulary development. Employing a descriptive qualitative approach, data were collected from ten students who engaged with the app over a period, completing exercises like “Guess the Word” and “Guess the Picture.” The results reveal notable vocabulary acquisition, with the highest mastery in categories such as colors (100%), numbers (90%) and fruits (80%), while vegetables showed the lowest (60%). The study attributes these differences to varying levels of exposure and cognitive simplicity of each vocabulary type that combines visual aids, auditory cues, and interactive exercises, promoting engagement and motivation compared to conventional learning. The study recommends refining the app to better support challenging vocabulary areas and offers significant benefits, particularly in vocabulary retention and positive learner attitudes.